Improved Osteogenesis of Selective-Laser-Melted Titanium Alloy by Coating Strontium-Doped Phosphate With High-Efficiency Air-Plasma Treatment - Xing, Haiyuan; Li, Ruiyan; Wei, Yongjie; Ying, Boda; Li, Dongdong; Qin, Yanguo (Frontiers in Bioengineering and Biotechnology, 2020)
Surface treatment and bioactive metal ion incorporation are effective methods for the modification of titanium alloys to be used as biomaterials. However, few studies have demonstrated the use of air-plasma treatment in orthopedic biomaterial development. Additionally, no study has performed a direct comparison between unmodified titanium alloys and air-plasma-treated alloys with respect to their biocompatibility and osteogenesis. In this study, the biological activities of unmodified titanium alloys, air-plasma-treated titanium alloys, and air-plasma-treated strontium-doped/undoped calcium phosphate (CaP) coatings were compared. The strontium-doped CaP (Sr-CaP) coating on titanium alloys were produced by selective laser melting (SLM) technology as well as micro-arc oxidation (MAO) and air-plasma treatment. The results revealed that rapid air-plasma treatment improved the biocompatibility of titanium alloys and that Sr-CaP coating together with air-plasma treatment significantly enhanced both the biocompatibility and osteogenic differentiation of bone marrow mesenchymal stem cells (BMSCs). Overall, this study demonstrated that low temperature air-plasma treatment is a fast and effective surface modification which improves the biocompatibility of titanium alloys. Additionally, air-plasma-treated Sr-CaP coatings have numerous practical applications and may provide researchers with new tools to assist in the development of orthopedic implants.